Implementación de un biodigestor para la obtención de biogas a partir de los excrementos de los animales de granja ubicada en el cantón Salcedo. - Acosta Clavijo, Jessica Maricela (2020)
The lack of treatment in farm animal waste causes contamination to the aquifers and the impossibility of using renewable energy to the environment, due to this problem, the design, construction and implementation of a biodigester for small farms was carried out in this project. In the theoretical foundation of the different types of biodigesters it was established that the family type is the most appropriate according to the indicators and amount of biomass available in the farm. In addition the procedure for the calculation of the different work parameters was established based on the internal reactor temperature, internal pressure generated, pH level and retention time. A greenhouse was also implemented to keep the biodigester protected from high winds and maintain the proper temperature in the digestion process. The results show a liquid volume of 0.386 m³, average temperature of 23.25 °C and system pressure of 11,197 mbar, for the sixth week 804.12 ppm was obtained in maximum concentration of methane gas (CH4), generating 0.549 m³ of biogas a month two weeks. The total cost of implementing the biodigester is $ 1210.98 and the recovery time of the initial investment is two and a half years.